2013
DOI: 10.1002/cne.23377
|View full text |Cite
|
Sign up to set email alerts
|

Cortical connections to single digit representations in area 3b of somatosensory cortex in squirrel monkeys and prosimian galagos

Abstract: The ventral posterior nucleus of thalamus sends highly segregated inputs into each digit representation in area 3b of primary somatosensory cortex. However, the spatial organization of the connections that link digit representations of areas 3b with other somatosensory areas is less understood. Here we examined the cortical inputs to individual digit representations of area 3b in four squirrel monkeys and one prosimian galago. Retrograde tracers were injected into neurophysiologically defined representations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 94 publications
4
48
1
Order By: Relevance
“…We identified topographic maps of the hand and face regions in area 3b and the hand region in area 1 from these four monkeys with long recovery times after DCLs. As previously described by Sur et al (), we found that the hand and face regions in area 3b were normally organized in a somatotopic manner (Liao et al, ). Representations of digits 1–5 were arranged in an orderly lateral‐to‐medial sequence in the rostral aspect of area 3b, with the representation of the palm located caudally.…”
Section: Resultssupporting
confidence: 81%
“…We identified topographic maps of the hand and face regions in area 3b and the hand region in area 1 from these four monkeys with long recovery times after DCLs. As previously described by Sur et al (), we found that the hand and face regions in area 3b were normally organized in a somatotopic manner (Liao et al, ). Representations of digits 1–5 were arranged in an orderly lateral‐to‐medial sequence in the rostral aspect of area 3b, with the representation of the palm located caudally.…”
Section: Resultssupporting
confidence: 81%
“…6A), the pattern of CO dense clusters less clearly matched the normal patterns seen in case MM-N, and appeared to be disordered and different on the two sides. The arrangement of VGLUT2-dense patches, which reflect the terminations of dorsal column afferents (Liao et al 2013), also showed these differences. In the right GrN, with inputs from a normal appearing foot, multiple patches of labeled axons were apparent in approximately normal dorsal and ventral locations for the P3 and PTH injections, respectively (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Tissue was processed for CO, and Nissl staining in the separate series to reveal cortical and thalamic architectures as previously described (Qi et al 2011b; Wong-Riley 1979). The sections processed for the VGLUT2 used a mouse monoclonal anti-VGLUT2 primary antibody (Millipore, Billerica, MA), which was characterized in previous publications (Balaram et al 2013; Liao et al 2013). …”
Section: Methodsmentioning
confidence: 99%
“…4.2) (Woolsey and Van der Loos 1970). Other examples include the cortical representation of the rays of the nose in star nosed moles (Catania and Kaas 1995), and the modular representation of the digits of the forepaw in moles (Catania and Kaas 1995), raccoons (Welker and Seidenstein 1959) and monkeys (Jain et al 1998;Qi and Kaas 2004;Liao et al 2013). These discrete clusters and bands of neurons for a particular input are separated from each other, and isolated from other similar inputs, by narrow-cell poor septa that occasionally contain enough neurons to form another type of processing module, as in the case of the barrel and septal systems in somatosensory cortex of rodents (Woolsey and Van der Loos 1970).…”
Section: Ocular Dominance Columns and Other Modules Representing Sepamentioning
confidence: 97%
“…As the septa and barrels have neurons with different response characteristics, they can be considered to represent two types of classical columns. Scale bar is 250 um cortex of monkeys (Jain et al 1998;Qi et al 2011;Liao et al 2013), and other patches of cortex for the teeth and for the tongue are separated by cell-poor regions as well (Kaas et al 2006;Cerkevich et al 2013).…”
Section: Classical Columnsmentioning
confidence: 99%